Validitas Lembar Kerja Mahasiswa (LKM) Untuk Menumbuhkan Motivasi Belajar Pada Matakuliah Kalkulus Lanjut Di Masa Pandemi Covid-19 - Muhammad Taqwa (STKIP Andi Matappa, 2021)
The Corona Virus Disease pandemic (Covid-19) requires that conduct online learning and independently including advanced calculus courses. Learning requires students to have a strong motivation to study. The development of Student Worksheets (SW) is a strategy that can foster student motivation. The purpose of this study was to develop a valid SW in growing student motivation. This kind of research was development research, namely the development of SW with the Plomp model: (1) initial investigation, (2) design, (3) realization/ construction, (4) tests, evaluations and revisions, (5) implementation. The subjects of this research were students of Mathematics Education Program in STKIP Andi Matappa. Research instruments: SW validation sheet. The results of the study: the content validity score of the SW is included in the high category. This shows that advanced calculus SW that has been developed meets valid to foster student motivation